Comparative analysis of the NLR gene family in the genomes of garden asparagus (Asparagus officinalis) and its wild relatives - Sun, Li-Ping; Zhai, Wen-Zhuo; Song, Rui-Yan; Ning, Hao-Han; Li, Shu-Fen; Gao, Wu-Jun (Frontiers in Plant Science, 2025)
Garden asparagus (Asparagus officinalis), a prominent horticultural crop recognized as the “king of vegetables” in the international market, is usually threatened by severe disease challenges that hinder its sustainable cultivation. Nucleotide-binding leucine-rich repeat receptors (NLRs) are key components of plant immune systems, yet their specific role and evolutionary patterns in A. officinalis and its related species remain poorly characterized. In this study, we conducted a comprehensive analysis of NLR gene distribution patterns, structural features, phylogenetic characterization, and evolutionary dynamics across A. officinalis and two phylogenetically related species, Asparagus kiusianus and Asparagus setaceus, and conducted expression studies after Phomopsis asparagi infection in A. officinalis. Our findings demonstrate that NLR genes in all three species display chromosomal clustering patterns. Phylogenetic reconstruction and N-terminal domain classification categorized these NLRs into three distinct subfamilies, with their promoters containing numerous cis-elements responsive to defense signals and phytohormones. Comparative genomic analysis revealed a marked contraction of the NLR genes from the wild species to the domesticated A. officinalis, with gene counts of 63, 47, and 27 NLR genes identified in A. setaceus, A. kiusianus, and A. officinalis, respectively. Orthologous gene analysis identified 16 conserved NLR gene pairs between A. setaceus and A. officinalis, which are likely the NLR genes preserved during the domestication process of A. officinalis. Pathogen inoculation assays revealed distinct phenotypic responses: A. officinalis was susceptible, while A. setaceus remained asymptomatic. Notably, the majority of preserved NLR genes in A. officinalis demonstrated either unchanged or downregulated expression following fungal challenge, indicating a potential functional impairment in disease resistance mechanisms. In conclusion, our findings suggest that the increased disease susceptibility of domesticated A. officinalis is driven by both the contraction of NLR gene repertoire and the functional reduced or inconsistent induction of retained NLR genes—potentially a consequence of artificial selection favoring yield and quality. This study provides important insights into the evolutionary dynamics of NLR genes within the Asparagus genus and may contribute to future efforts aimed at disease-resistant breeding in A. officinalis.